2015
DOI: 10.1080/2162402x.2015.1021537
|View full text |Cite
|
Sign up to set email alerts
|

Identification of characteristic TRB V usage in HBV-associated HCC by using differential expression profiling analysis

Abstract: Liver cancer is one of the most common cancers worldwide. CDR3 sequencing-based immune repertoire can be closely associated with cancer prognosis and development. Identifying the specific interaction between the TCR and cellular antigens is important for developing novel immunotherapeutic approaches for the treatment of cancer. The rearranged TCRβ loci amplified using Vβ- and Jβ-specific primers by multi-PCR and sequenced using high-throughput sequencing (HTS) in liver cancers were compared with those of T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…By high throughput TCR sequencing of T‐cell repertoires, differential TCR signatures had been identified in primary biliary cirrhosis, primary sclerosing cholangitis, and alcoholic liver disease, which represented an imprint of distinctive antigenic repertoires in these chronic liver diseases 13. Similarly, significant differences of T‐cell repertoires among HCC, intrahepatic cholangiocarcinoma, and mixed hepatocellular and cholangiocellular carcinoma have also been demonstrated 14. Besides, the T‐cell repertoires in tumor and matched adjacent nontumor tissues from HBV‐associated HCC patients have also shown a significant difference, suggesting a distinct T cell immune microenvironment 15.…”
Section: Introductionmentioning
confidence: 99%
“…By high throughput TCR sequencing of T‐cell repertoires, differential TCR signatures had been identified in primary biliary cirrhosis, primary sclerosing cholangitis, and alcoholic liver disease, which represented an imprint of distinctive antigenic repertoires in these chronic liver diseases 13. Similarly, significant differences of T‐cell repertoires among HCC, intrahepatic cholangiocarcinoma, and mixed hepatocellular and cholangiocellular carcinoma have also been demonstrated 14. Besides, the T‐cell repertoires in tumor and matched adjacent nontumor tissues from HBV‐associated HCC patients have also shown a significant difference, suggesting a distinct T cell immune microenvironment 15.…”
Section: Introductionmentioning
confidence: 99%
“…A unique CDR3 clone whose reads account for .0.1% of total reads stands for a "highly expressed clone" (HEC-unique CDR3) (22). A lineage whose reads from all unique CDR3s account for .0.1% of the total reads represents a "highly expanded and expressed clone" (HEC-lineage) (22).…”
Section: Reduced Clonal Diversity and Enhanced Clonal Expansion And Ementioning
confidence: 99%
“…A unique CDR3 clone whose reads account for .0.1% of total reads stands for a "highly expressed clone" (HEC-unique CDR3) (22). A lineage whose reads from all unique CDR3s account for .0.1% of the total reads represents a "highly expanded and expressed clone" (HEC-lineage) (22). The ratio of HEC-lineage numbers to total lineage numbers was referred to as HEC-lineage number rate, and so was the HEC-unique CDR3 number rate, both of which were used to reflect the degree of clonal expansion and expression.…”
Section: Reduced Clonal Diversity and Enhanced Clonal Expansion And Ementioning
confidence: 99%
“…[14][15][16] A recent investigation of HBV-associated HCC indicated that the highly expanded clone (HEC) ratio of TCRb CDR3 (TRB CDR3) was significantly different in liver cancer compared to healthy and hepatitis B patients. 17 The comparison of TRB CDR3 among three histological types of liver cancer samples revealed that the consistency between tumor tissues and adjacent non-tumor tissues was related to tumor malignancy. However, because HBV-associated HCC develops as a result of HBV infection, the immune microenvironments differ between tumor and adjacent non-tumor tissues, and the consequent TRB CDR3 diversity should be elucidated, respectively.…”
Section: Introductionmentioning
confidence: 99%